NOVEL BUNGA-BUNGA KERTAS KARYA KHUSNUL KHOTIMAH ANALISIS PSIKOLOGI SASTRA - Wiguna, Ketut Indria (Humanis, 2013)
The object of the research is the novel written by Khusnul Khotimah with the title Bunga-Bunga Kertas. It was chosen since one of the character named Bunga has the most prominent psychological dilemmas. There are aims of this study, the first is to identify the plot, the setting and deceiving of the character, the second is to find out the relation between the elements, the third is to determine the psychological aspect of the character. There are two theories were used in this study, the first one is the theory of the personality structure, and the other theory is the theory of development phase.The findings of this research show that the people who have strong personality will be able to face the problems in life.
Keywords: personality, development, psychological